Agricultural Teachers' Attitude towards Teaching Profession - Balakrishnan, Renu; Singh , Premlata; Varghese, Eldho; Murai, Ashish Santosh (Indian Journal of Extension Education, 2018)
Attitude is a feeling of like, dislike, attraction, repulsion, interest or apathy towards other persons, objects or ideas.  Teachers have a huge role to play in realizing future agricultural revolutions by guiding and mentoring agricultural higher  education students. Therefore, it is very much necessary to know that how the agricultural teachers feel about their  profession and what the reasons are behind having such feelings. The study was undertaken in four reputed Agricultural  Universities of India: ICAR- IARI, New Delhi; ICAR- NDRI, Karnal; TNAU, Coimbatore and UAS, Bangalore  constituting a total sample size of 180 agricultural teachers. The study revealed that agricultural teachers in these  universities had a positive attitude towards teaching.
Keywords: Attitude; agriculture; teacher; teaching; profersion